The Impact of Land Commodification on Small and Landless Farmer’s Access to Rent Land in the Sub-Urban Village - Hudayana, Bambang (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
Intisari: Artikel ini membahas akses petani untuk menyewa lahan untuk pertanian padi di desa di pinggir Yogyakarta. Penelitian ini menggunakan teori ekonomi politik untuk mendeskripsikan beroperasinya kelembagaan penyewaan lahan. Pengumpulan data dilakukan melalui wawancara mendalam dengan informan kunci, observasi dan survei. Informan kunci itu adalah seorang pejabat desa, dua kepala sub-desa, tiga ketua kelompok tani, dan lima penyewa tanah. Mereka diwawancarai tentang berbagai bentuk lembaga penyewaan tanah, posisi dan kuasa para pelaku dalam praktik penyewaan tanah. Pengamatan dilakukan untuk mengidentifikasi penggunaan lahan yang menjadi objek sewa, dan survei dilakukan di tiga dusun sampel untuk menghitung jumlah petani dan pengusaha agribisnis dan nonpertanian yang menyewa lahan. Hasil penelitian menunjukkan bahwa petani kecil dan petani tunakisma menyewa lahan untuk ketahanan pangan. Ada tiga jenis lahan yang menjadi objek sewa, yaitu tanah milik pribadi, bengkok sebagai gaji pegawai desa, dan tanah kas desa. Komodifikasi telah mengurangi akses petani kecil dan petani tunakisma untuk menyewa lahan, khususnya tanah bengkok dan kas desa. Sebaliknya, komodifikasi telah meningkatkan akses lahan bagi pelaku agribisnis dan investor di sektor nonpertanian. Kata kunci: Petani kecil dan tunakisma; komodifikasi lahan; institusi penyewaan tanah; tanah privat; bengkok; tanah kas desa This article discusses farmers’ access to rent land for rice farming in a suburban village on the outskirts of Yogyakarta. This study uses a political economy theory to describe the operation of land leasing institutions. Data collection was carried out through in-depth interviews with key informants, observations and surveys. The key informants were a village official, two sub-village heads, three farmer group leaders, and five land tenants. They were interviewed on the various forms of land leasing institutions, the positions and powers of actors in land leasing practices. Observations were conducted to identify land uses that were the object of lease, and surveys were conducted in three sample sub-villages to calculate the number of farmers and agribusiness and non-agricultural businessmen who rented land. The results showed that small farmers and landless farmers rent land for food security. There are three types of land that are the object of lease, namely privately owned land, bengkok as village employee salaries, and village treasury land. The commodification has reduced the access of smallholders and landless farmers to rent land, especially bengkok land and village treasuries. Conversely, commodification has increased land access for agribusiness actors and investors in the non-agricultural sector.